A Breach in Anthropocentrism and Speciesism? Changes in Cultural Consciousness on the Example of the Relationship: Human – Non-human Animal Species in the Second Half of the Nineteenth Century - Sobieraj, Tomasz (Porównania, 2021)
The article contains an interpretation of selected Polish popular science and cultural texts published in the second half of the nineteenth century. All of them were devoted to the relationship: human – nonhuman animals and the status of the latter in human society. These texts – written by positivists and naturalists – show the changes which European cultural awareness has undergone. They consisted in a gradual abandonment of anthropocentric thinking and speciesism. All the authors protested against inflicting suffering and persecution of animals. Under the influence of Darwin and the development of 19th-century natural science, a breakthrough in the perception of the human condition and its relationship with animals took place. Although not without resistance and difficulties, animals began to be treated as living beings, susceptible to suffering, with a rich mental life. Many scientists and intellectuals began challenging the traditional view of the status of nonhuman animals dominated by anthropocentric stereotypes.